2020
DOI: 10.1021/acsnano.0c02745
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Selective Synthesis of MoS2 and WS2 Structures under Ambient Conditions for Customized Electronics

Abstract: Transition metal dichalcogenides (TMDs) have attracted significant interest as one of the key materials in future electronics such as logic devices, optoelectrical devices, and wearable electronics. However, a complicated synthesis method and multistep processes for device fabrication pose major hurdles for their practical applications. Here, we introduce a direct and rapid method for layer-selective synthesis of MoS 2 and WS 2 structures in wafer-scale using a pulsed laser annealing system (λ = 1.06 μm, pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 33 publications
(43 reference statements)
1
56
1
Order By: Relevance
“…More importantly, this method has excellent controllability and the obtained films scale is up to 1.412 cm. Subsequently, Park et al 69 reported an approach to induce a local photothermal decomposition reaction of ammonium tetrathiomolybdate and ammonium tetrathiotungstate precursor resulting in thermal deposited MoS 2 and WS 2 thin films utilizing photothermal effect of infrared laser, and then to prepare vdWHs in the substrate directly. Laser synthesis method has good advantages in controllable and selective synthesis, however, it is necessary to further study of larger size and monolayer materials growth due to the restrict of laser.…”
Section: Preparation Of Tmdcsmentioning
confidence: 99%
“…More importantly, this method has excellent controllability and the obtained films scale is up to 1.412 cm. Subsequently, Park et al 69 reported an approach to induce a local photothermal decomposition reaction of ammonium tetrathiomolybdate and ammonium tetrathiotungstate precursor resulting in thermal deposited MoS 2 and WS 2 thin films utilizing photothermal effect of infrared laser, and then to prepare vdWHs in the substrate directly. Laser synthesis method has good advantages in controllable and selective synthesis, however, it is necessary to further study of larger size and monolayer materials growth due to the restrict of laser.…”
Section: Preparation Of Tmdcsmentioning
confidence: 99%
“…3(a)]. The precursor nuclei in the solution continuously adhere to the SiO 2 /Si substrate; Park et al [23] have recently developed a novel process that can freely form TMDC patterns through a pulsed laser annealing method. Using the precursor deposition method of Yang et al [20], a precursor is initially deposited on a 4-inch TMDC thin film by spin coating.…”
Section: Synthesis Of Direct-patterned Tmdc Filmsmentioning
confidence: 99%
“…The analyzed photo responsivity of the fabricated device is ~5.39 A W -1 , which is higher than that of the previously reported TMDC-based optoelectronic devices that are made up of monolayer homo-and heterojunctions. Park et al [23] demonstrated a p-n diode with vertically stacked solution-processed WS 2 /MoS 2 thin films prepared by irradiating (NH 4 ) 2 WS 4 /MoS 2 films with an ultra-short laser pulse (~100 ps) to cause selective thermolysis of (NH 4 ) 2 WS 4 , since it shows ~60 times higher absorbance than the MoS 2 film during the laser annealing (1.06 μm). The process converts (NH 4 ) 2 WS 4 to a WS 2 film with high crystallinity despite the instant formatting on the MoS 2 lattice.…”
Section: Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since monolayer graphene is a gapless semiconductor, it has no useful applications in the semiconductor industry, logic, and spintronic devices. Within the 2D materials, monolayer molybdenum disulfide (MoS 2 ) was successfully synthesized via several experimental techniques 3 7 . Unlike graphene, the monolayer MoS 2 is a direct bandgap semiconductor with a tunable bandgap 8 .…”
Section: Introductionmentioning
confidence: 99%